2022
DOI: 10.3847/1538-3881/ac5f49
|View full text |Cite
|
Sign up to set email alerts
|

Zeta-Payne: A Fully Automated Spectrum Analysis Algorithm for the Milky Way Mapper Program of the SDSS-V Survey

Abstract: The Sloan Digital Sky Survey (SDSS) has recently initiated its fifth survey generation (SDSS-V), with a central focus on stellar spectroscopy. In particular, SDSS-V's Milky Way Mapper program will deliver multiepoch optical and near-infrared spectra for more than 5 × 106 stars across the entire sky, covering a large range in stellar mass, surface temperature, evolutionary stage, and age. About 10% of those spectra will be of hot stars of OBAF spectral types, for whose analysis no established survey pipelines e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
(76 reference statements)
1
13
0
Order By: Relevance
“…We used the zeta-Payne (Straumit et al 2022) spectrum analysis algorithm to analyse the averaged spectra of the 98 Galactic single stars or SB1 systems. The zeta-Payne is a machine learning framework that trains a neural network on a grid of synthetic spectra to obtain a spectrum interpolator.…”
Section: Spectrum Analysis With the Zeta-paynementioning
confidence: 99%
See 1 more Smart Citation
“…We used the zeta-Payne (Straumit et al 2022) spectrum analysis algorithm to analyse the averaged spectra of the 98 Galactic single stars or SB1 systems. The zeta-Payne is a machine learning framework that trains a neural network on a grid of synthetic spectra to obtain a spectrum interpolator.…”
Section: Spectrum Analysis With the Zeta-paynementioning
confidence: 99%
“…In this paper, we analyse the spectra of 166 B-type stars that exhibit photometric variability in their TESS light curves, with the purpose of future combined asteroseismic and spectroscopic modelling. For the sake of efficiency and consistency of the obtained results across the entire stellar sample, we employ the zeta-Payne (Straumit et al 2022) machine learning-based spectrum analysis algorithm. The method is a generalisation of the originally proposed The Payne algorithm (Ting et al 2019) towards the inclusion of a model with an a priori unknown residual instrumental response function into the parameter vector.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore easier to compute. Straumit et al (2022) pointed out that for high-resolution spectra, the neural network performs worse in regions of the parameter space with low values of v sin i and temperatures in the late-A to F-type regime. This is due to the many narrow spectral lines that have to be resolved by the neural network in this regime.…”
Section: Spectrum Analysis With Zeta-paynementioning
confidence: 99%
“…We used the constant resolution value of FEROS because the LSF computed from the ThAr frames that were taken during the observing run changes from night to night. The neural network was trained in the same way as described in Straumit et al (2022); more information can be found in that paper. For every star in the sample, surface parameters and the RV were derived by fitting model spectra to the observed spectrum using the neural network interpolator, performing a Doppler shift, and minimising the χ 2 merit function.…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation